G255(P) From A&E to the community, parents learn together through ABC. (25th October 2020) - Okereafor, A; Jenkins, C; Hahn, G; Kennedy, C; Okyere, B
Abstract : Problem and Aims: Our A&E department assesses 45, 000 children every year, 40% of these could be self-managed or treated in primary care. This proportion of inappropriate presentations is unsustainable and requires a radical community-based approach. We coproduced a community outreach project to: Educate and improve parents' confidence to deal with childhood illnesses and injuries. Decrease anxiety–related and avoidable A&E attendances by signposting alternative NHS services. Develop social support structures. Method: Paediatric staff invited families with: children under 1 year, limited social support or partial understanding of healthcare systems to collaborate on developing a programme of health education and social support. We facilitated groups discussing childhood illnesses and parental concerns. Parents reported 'fear of death' so we devised a programme including basic life support training. An online social network, local events, holiday sessions and weekly support groups were established to help address isolation and social inequalities. To expand our impact we contacted frequent A&E attenders, invited expectant parents, approached local health visitors and advertised through local GPs, schools and libraries. Results: Between May and June 2019 we ran four 1-hour sessions on common childhood problems each attended by 6–12 parents. 100% of parents reported increased learning and 100% joined the 'ABC Parents' WhatsApp group for ongoing support. Between May and October 2019 we conducted four free workshops delivering BLS, illness prevention, and health services education. Over two 3-hour sessions parents discussed child health concerns, experiences and services awareness. Out of 70 attendees, 97% reported feeling confident in managing childhood illnesses and 94% were more aware of local services and how to access them after the courses. To date there are 19 known avoided A&E attendances, with parents delivering care at home or using other NHS services. Conclusion: Coproduction with parents and collaboration with local organisations is a powerful and mutually beneficial mission. We increased parental health knowledge, confidence and avoided unnecessary A&E attendances. Our ABC Parents network is 'Achieving Better Communities of Parents' by providing support, resource signposting, poverty advice and our champions are expanding this paediatric community outreach for healthier children's futures.